At the Heart of Teacher Professional Development: Teachers Matter - Abdul Rahman (Indonesian Journal of Learning Education and Counseling, 2021)
This paper focuses on the influence of teacher characteristics on teacher professional development (TPD) practices. It draws upon a multiple-case study of teachers’ professional development experiences at three schools. Data were gathered through questionnaires and semi-structured interviews. Teachers’ characteristics matter in any professional development activities but not at the same level of influence to make TPD effective. Formal characteristics such as years of teaching experiences, level of studies and status of employment have always tended to greatly affect the level of teachers’ TPD participation. It is found, however, that teachers’ level of TPD participation does not always equate learning. It is teachers’ personal and professional characteristics such as beliefs about their roles or profession and perspectives of effective TPD that carry profound effects on teachers’ experimentation, application and reflection of TPD ideas for meaningful learning to occur, and enact the expected changes or improvements accordingly.